(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this research, the recovery of copper from copper slag is investigated using hydrometallurgy method. Slag samples were taken from Al-Shaheed State Company. The results of the chemical analysis showed that the slag contained 11.4% of copper. The recovery process included two stages; the first stage is leaching using diluted sulfuric acid. The most important variables that effect on the leaching process was studied, such as acid concentration, hydrogen peroxide adding, particle size, liquid to solid, stirring speed and leaching time by changing the condition and the stabilizing of other factors at room temperature. The second stage is precipitation of copper from leaching solution by zinc powder with different weights and times, at room temperature and 1.5 PH value. The results of the first stage manifested that about 99.7% of the copper have been dissolved at the following operational conditions: 50% acid concentration, 5 ml hydrogen peroxide adding, particle size (-75+53) micron, 1:10 liquid to solid, 500 rpm stirring speed and 25 min of leaching time. The highest percentage of copper precipitation in the second stage was 99.8% when added 3gm zinc powder at 20 min. The XRD result revealed that the predominant phase was pure copper. The results of EDS exhibited that a few percentage of oxygen appeared with copper powder. The final of copper recovery ratio was 99.3% with 99.2% purity.